2013
DOI: 10.1080/09687599.2012.728795
|View full text |Cite
|
Sign up to set email alerts
|

How do men with paraplegia choose activities in the light of striving for optimal participation? A qualitative study, based on a phenomenological–hermeneutical method

Abstract: The objective of this study was to explore the experiences of men with paraplegia with regard to how they choose activities. The study involved a qualitative research design, based on a phenomenological-hermeneutical method. The findings revealed that the activities participants were choosing could be on a continuum between the individual's self and the influence from their environment. On this continuum, the choice to perform activities was influenced by two mediating factors: the individual's activities perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 33 publications
0
26
0
Order By: Relevance
“…Participants were forced into passivity by social expectations of compliance, overprotection, being given choices that were not genuine, and environmental barriers. Worry about being an imposition on others 30,43,48,53 or potential retribution if they were not friendly 50 diminished their power and, hence, decreased control over their life. Some participants described their experience in institutional care as being at the "mercy of staff" 41(p611) and because of their reliance on caregivers 28,43,48 they placed their needs secondary and did not complain.…”
Section: Enforced Passivitymentioning
confidence: 99%
See 3 more Smart Citations
“…Participants were forced into passivity by social expectations of compliance, overprotection, being given choices that were not genuine, and environmental barriers. Worry about being an imposition on others 30,43,48,53 or potential retribution if they were not friendly 50 diminished their power and, hence, decreased control over their life. Some participants described their experience in institutional care as being at the "mercy of staff" 41(p611) and because of their reliance on caregivers 28,43,48 they placed their needs secondary and did not complain.…”
Section: Enforced Passivitymentioning
confidence: 99%
“…48,49 However, to ensure security, participants could also make a conscious choice to be passive and accepting. 31,42,53 Passivity was encouraged when participants found themselves obligated to permanently adopt roles they were "steered" 53(p652) toward by well-meaning family members or health professionals. 30,38,48,53 When participants were not properly included in decisions about role choices, they were perceived as ingenuine.…”
Section: Enforced Passivitymentioning
confidence: 99%
See 2 more Smart Citations
“…The stories reflected considerable variability in how participants contributed, perhaps owing to differences in personality, experience and place. Van de Velde et al (2013) suggested that persons with SCI benefit from being able to choose activities that fit with their sense of self, their environment, activities they did before their injury and expectations of the future. What seems to be important is not how people contribute, but rather that they just do so.…”
Section: Contributingmentioning
confidence: 99%